Present trends in the detection of myocardial viability in nuclear cardiology - Amalia Peix González; David García Barreto (ECIMED, 2014)
The myocardial viability diagnosis is important for those who will underge myocardial revascularization wither by surgery or coronary angioplasty. Our purpose is to present some of the present trends in the detection of myocardial viability using nuclear cardiology tests. Emphasis is made on the estimation of radiopharmaceutical uptake and the use of vasodilators in perfusion scintigraphy mainly with technetium-labeled compounds. Also, the current possibilities for a myocardial metabolism study using single-photon emission-computed tomography as well as some clinical implications of myocardial viability are set forth.